Analysis and experiment of the film-soil separation mechanism of the residual film recovery machine in the plough layer - Shen, Shilong; Zhang, Jiaxi; Wang, Yichao; Wang, Zhenwei; Li, Jinming; Dong, Wenhao (International Journal of Agricultural and Biological Engineering, 2025)
In order to solve the problems of unclear film separation in traditional topsoil residual film recovery machine and secondary broken film caused by the toot-shaped structure, a film-soil conveying and vibration separation device was designed. It mainly consists of a first-level vibration conveying chain, roller extrusion and crushing mechanism and secondary conveyor chain, which can complete the functions of conveying, vibration separation, and crushing separation of film-soil composite. Firstly, the mechanical model of the transport process of the film-soil composite was established, and the transport stability of the film-soil composite was analyzed. The vibration characteristics of the vibration mechanism were analyzed by analytical method, and the vibration model of the vibration mechanism was established. The distribution state of residual film-soil mixture was observed and measured by high-speed camera, and the influence of vibration wheel speed and installation distance on the distribution height of residual film-soil mixture was found out. The crushing mechanism of the residual film-soil composite was proved by studying the roller extrusion and crushing mechanism. The Box-Behnken response surface test method was used to carry out field tests on the transport and vibration separation device of film-soil with soil content rate and film leakage rate as evaluation indices. The results indicated that the influencing factors on the soil content rate in a dscending order are conveyor chain speed, vibration wheel speed, and installation distance. In contrast, the factors affecting the film leakage rate, also ranked from largest to smallest, are conveyor chain speed, installation distance, and vibration wheel speed. The combination of film-soil separation parameters is as follows: conveying chain speed is 1.6 km/h, vibration wheel speed is 189.7 r/min, installation distance is 769.7 mm, at this time the soil content rate is 18.31%, and the film leakage rate is 9.49%, which meet the requirements of the recovery of residual film in the plough layer. The conveying and vibration model established in this study can provide a theoretical basis and technical reference for elucidating the soil-film separation process. Keywords: residual film, film-soil conveying and vibration separation device, film-soil composite, steady transportation, vibration mechanism, crushing mechanism, field tests DOI: 10.25165/j.ijabe.20251805.9800 Citation: Shen S L, Zhang J X, wang Y C, Wang Z W, Li J M, Dong W H. Analysis and experiment of film-soil separation mechanism of the residual film recovery machine in the plough layer. Int J Agric & Biol Eng, 2025; 18(5): 181–190.